Cognitive Semantics Against Creole Exceptionalism: A Case Study of Body Part Expressions in Nigerian Pidgin - Kosecki Krzysztof (Studies in Logic, Grammar and Rhetoric)
One of the claims of creole exceptionalism is that creole languages have lexicons of reduced conceptual and expressive complexity. Building on previous studies of the lexicon of Nigerian Pidgin/NP and the applications of the cognitive linguistic framework in creole linguistics, the present paper aims to counter the exceptionalism claim by analysing the conceptual structure of body part expressions in NP. It is argued that the expressions not only involve embodied universal patterns of imaginative reasoning, but also blend the substratum patterns of West African languages with the superstratum influence of colonial lexifiers, especially English. Thanks to this, NP speakers can deal with diverse aspects of experience, such as emotions, mental life, social interaction, or business transactions, which is strong evidence for the complex conceptual structure and the richly expressive character of the NP lexicon.